Assessing the feasibility of single target radiosurgery quality assurance with portal dosimetry. Issue 5 (1st April 2019) - Covington, Elizabeth L.; Snyder, Jesse D.; Wu, Xingen; Cardan, Rex A.; Popple, Richard A.
Abstract: Purpose: To assess the feasibility of using portal dosimetry (PD) for pre‐treatment quality assurance of single target, flattening filter free (FFF), volumetric arc therapy intracranial radiosurgery plans. Methods: A PD algorithm was created for a 10X FFF beam on a Varian Edge linear accelerator (Varian Inc, Palo Alto, CA, USA). Treatment plans that were previously evaluated with Gafchromic EBT‐XD (Ashland, Bridgewater, NJ, USA) film were measured via PD and analyzed with the ARIA Portal Dosimetry workspace. Absolute dose evaluation for film and PD was done by computing the mean dose in the region receiving greater than or equal to 90% of the max dose and comparing to the mean dose in the same region calculated by the treatment planning system (TPS). Gamma analysis with 10% threshold and 3%/2 mm passing criteria was performed on film and portal images. Results: Thirty‐six PD verification plans were delivered and analyzed. The average PD to TPS dose was 0.989 ± 0.01 while film to TPS dose was 1.026 ± 0.01. All PD plans passed the gamma analysis with 100% of points having gamma <1. Overall, PD to TPS dose agreement was found to be target size dependent. As target size decreases, PD to TPS dose ratio decreased from 1.004 for targets with diameters between 15–31 mm and 0.978 for targets with diameters less than 15 mm. Conclusion: The agreement of PD to TPS mean dose in the high dose region was found to be dependent on target size. Film measurements did not exhibit size dependence. All PD plans passed the 3%/2 mm gamma analysis, but caution should be used when using PD to assess overall dosimetric accuracy of the treatment plan for small targets.